Development, validation and application of a LC-MS/MS method for quantification of 15 cannabinoids in food. (15th July 2020) - Christinat, Nicolas; Savoy, Marie-Claude; Mottier, Pascal
Highlights: A LC-MS/MS method for the quantification of 15 cannabinoids in food was validated. Cannabidiol and cannabidiolic acid were widely detected in twenty food products. Low level of cannabidiol was measured in a milk sample produced by hemp-fed cows. Abstract: In this study, the occurrence of cannabinoids in hemp-based food products was investigated. For that purpose, a new liquid chromatography tandem mass spectrometry method for the quantification of fifteen cannabinoids was developed and validated for multiple matrices. Method performances were good, fulfilling the SANTE/11813/2017 requirements, and allowing for products compliance testing with various national legislations on cannabinoids levels in food products. The limit of quantification of each analyte was 0.15 mg/kg for hemp seed and hemp protein, 0.6 mg/kg for hemp seed oil, and 0.005 mg/kg for raw milk and milk powder. The applicability of the method was further demonstrated by conducting a limited survey on twenty hemp-based food products. The survey revealed that products from the same category can have very different cannabinoids profiles and levels. These results highlighted the importance of cannabinoids testing of food products in view of the current heterogeneous and fast evolving regulatory landscape worldwide.